PERANCANGAN MESIN REFRIGERASI KOMPRESI UAP PENYIMPAN TELUR AYAM - Hendradinata, Hendradinata (Universitas Tridinanti Palembang, 2018)
Cooling Machine for eggs Storage are needed to keep the quality for storage for a long time. The purpose of this research is to design egg storage machine to be guaranteed Nutritional Value, Quality and economic. This plan begins by calculating the coolant load, determining the storage design and the component of the refrigeration component. Based on the results of analysis to store eggs with a capacity of 20 Kg with the dimensions of Length (P) x Width (L) x Height (T) = 70 cm x 70 cm x 80 cm, Found that the Transmission load is 32.1195 Watt, Infiltration load is 1.3853 watts and Product load = 18.692 watts. The required compressor capacity is 21.796455 W. The required Evaporator capacity is 0.1021338 kW and the required Condenser capacity is 123,930255 Watt. Â Keywords: Cooling Machine, design-build, cooling load